PENGARUH MINAT BELAJAR DARING TERHADAP HASIL BELAJAR MATA PELAJARAN PENJASKES PADA SISWA KELAS XI SMAN 5 TUALANG - Febrianto, Rian; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the Covid-19 pandemic which requires all educational institutions in Indonesia to implement an online learning system, therefore the purpose of this research is to find out whether there is an influence of online learning interest on physical education learning outcomes in Class XI students of SMAN 5 Tualang. This research was conducted in November – April 2022. The population in this study were class XI SMAN 5 Tualang, totaling 283 student. This study uses a convenience sampling technique, with a sample of 60 students who meet the criteria of the researchers taken from 2 classes. The instrument used in the research is primary data in the form of questionnaires filled in by students, semester exam sheets, and also documentation, using data analysis techniques in the form of percentage %. From the results of research based on the results of data analysis obtained, it can be concluded that the internal, external indicators and linear regression calculations on student interpretation show that most students' interest in online learning is very good, so it can be said that the influence of interest in online learning outcomes on students at SMA Negeri 5 Tualang is positive. That is, the level of student interest affects learning outcomes.Key Words: Physical Education, Online Learning, Interest